Motorcycle accident reconstruction - Rose, Nathan (SAE International, 2022)
Accident reconstruction utilizes principles of physics and empirical data to analyze the physical, electronic, video, audio, and testimonial evidence from a crash, to determine how and why the crash occurred, how the crash could have been avoided, or to determine whose description of the crash is most accurate. This process draws together aspects of mathematics, physics, engineering, materials science, human factors, and psychology, and combines analytical models with empirical test data. Different types of crashes produce different types of evidence and call for different analysis methods. Still, the basic philosophical approach of the reconstructionist is the same from crash type to crash type, as are the physical principles that are brought to bear on the analysis. This book covers a basic approach to accident reconstruction, including the underlying physical principles that are used, then details how this approach and the principles are applied when reconstructing motorcycle crashes. This second edition of Motorcycle Accident Reconstruction presents a thorough, systematic, and scientific overview of the available methods for reconstructing motorcycle crashes. This new edition contains: Additional theoretical models, examples, case studies, and test data. An updated bibliography incorporating the newest studies in the field. Expanded coverage of the braking capabilities of motorcyclists. Updated, refined, and expanded discussion of the decelerations of motorcycles sliding on the ground. A thoroughly rewritten and expanded discussion of motorcycle impacts with passenger vehicles. Updated coefficients of restitution for collisions between motorcycles and cars. A new and expanded discussion of using passenger car EDR data in motorcycle accident reconstruction. A new section covering recently published research on post-collision frozen speedometer readings on motorcycles. A new section on motorcycle interactions with potholes, roadway deterioration, and debris and expanded coverage of motorcycle falls. This second edition of Motorcycle Accident Reconstruction is a must-have title for accident reconstructionists, forensic engineers, and all interested in understanding why and how motorcycle crashes occur.